Pengujian Senyawa C-Sinamalkaliks[4]Resorsinarena Hasil Sintesis Dari Limbah Minyak Kayu Manis (Cinnamomum Burmanii) Sebagai Antioksidan - Susiyati Safitri; Sri Benti Etika (Departemen Kimia FMIPA UNP, 2022)
C-Sinamalkaliks[4]resorcinarene is the result of the reaction of cinnamaldehyde and resorcinol compounds derived from cinnamon oil waste which has four alkenyl groups (double bonds), eight hydroxyl groups, and twelve benzene residues so that it can be used as an antioxidant because it has an OH group. The purpose of this study was to determine the IC50 value and antioxidant activity of C-Sinamalkalix[4]resorcinarene using the DPPH method (2,2-Diphenyl-1-picrylhydrazyl) and the ABTS method (2,2'-azino-bis(3-ethylbenz). -thiazoline-6-sulfonic acid Test results of antioxidant activity on the compound C-Sinamalkaliks[4]resorcinarene using the DPPH method (2,2-Diphenyl-1-picrylhydrazyl) using a UV-Vis spectrophotometer at a maximum wavelength of 514 nm. IC50 of 161.1750 ppm with moderate antioxidant activity Testing the antioxidant activity of the compound C-Sinamalkaliks[4]resorcinarene using the ABTS method (2,2'-azino-bis(3-ethylbenz-thiazoline-6-sulfonic acid) using UV spectrophotometer-Vis is at a maximum wavelength of 750 nm, IC50 value is 2.9661 ppm with very strong antioxidant activity.